Spatial and Temporal Variation in the Quality of Summer Foods for Herbivores along a Latitudinal Gradient - Holá, Michaela (2013)
The spatial and temporal variation in nutritional quality of plants consumed by herbivores is considered as one of the main factors governing their feeding patterns and influencing their productivity. Plant nutrients vary in space and time both within and among plant species, at fine scales, and across large geographical scales, creating a heterogeneous environment where herbivores have to cope with variation in food quality at different spatiotemporal scales. As a response to this variation, herbivores make trade-offs between acquisition of digestible nutrients (e.g. nitrogen) and reduction of digestibility-reducing compounds (e.g. plant defence compounds like phenolics or tannins). Since little is known where the major sources of variation that herbivores face are and how these may be compared in a natural system, I analysed spatial and temporal variation in food quality (i.e. the concentration of nitrogen, fiber, total phenolics and condensed tannins) at three levels: local, regional and yearly scales. Two important plant species, downy birch (Betula pubescens) and fireweed (Epilobium angustifolium), in the summer diet of moose (Alces alces) were collected for three subsequent years along a latitudinal gradient of varying environmental conditions spanning across Sweden and assessed with near infrared reflectance spectroscopy. The degree of variation in nutritional aspects of food quality was of similar importance at all three spatiotemporal scales. In addition, there was a clear latitudinal gradient of these nutrients, where nitrogen and fiber increased towards the south in both species, and defence compounds increased towards the north in fireweed. My findings may have important implications for researchers dealing with multiple sources of variation in large scale questions, like climate change and its effects on plant-herbivore interactions.